Dual-Path Model of Team Communication and Shared Mental Models in Entrepreneurial Education: Enhancing Team Efficacy in Higher Education Using PLS-SEM - Shuangshuang Fan; Shali Wang; William Mbanyele; Yongliang Zhang (Systems, 2025)
This study explores the influence of team communication (TC) and shared mental models (SMMs) on entrepreneurial team efficacy (ETE) within the context of Chinese higher education, introducing a dual-path model to reconcile the discrepancy between policy expectations and practical outcomes in entrepreneurship education. Utilizing partial least squares structural equation modeling (PLS-SEM) on data from 475 university-based questionnaires from March to May in 2024 in China, the research reveals that structured internal communication significantly enhances the alignment of learning goals, teammate cognition, and activity synchronization, thereby fostering SMMs as a pivotal psychological infrastructure. The findings indicate that shared learning goals and cognitive convergence are primary drivers of task performance, whereas coordinated activity states are more influential in strengthening relational cohesion. The study challenges the conventional “communication frequency–efficacy paradox” by demonstrating distinct pathways through which internal and external communication mechanisms differentiated impact task and relational outcomes. Additionally, demographic analyses highlight that team maturity and age diversity positively correlate with task efficacy, while gender and disciplinary heterogeneity show no significant association. Theoretically, this research advances the understanding of team collaboration dynamics and contextualizes Western entrepreneurship theories within China’s collectivist framework. Practically, it provides robust, evidence-based strategies for refining communication protocols and enhancing both collaborative efficiency and innovation in entrepreneurial education settings.